IMPLEMENTASI TEORI TAKSONOMI BLOOM PADA MATEMATIKA KELAS 2 SD MUHAMMADIYAH 4 - yatini, Kasmi (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2023)
This study discusses about implementation of Bloom's Taxonomy in mathematics. This is intended to answer the problem how to implement this concept to student with three way, they are planning, implementing and evaluating. This research at SD Muhammadiyah 4 Surakarta Central Java Indonesia in the second grade with 2 teachers. This research uses a qualitative research approach. Technique data collection by interviews. The results showed that the teacher had determine 3 aspects of Bloom's Taxonomy, there is cognitive, affective, and psychomotor aspects. The implementation stage, the teacher applied the cognitive aspects at the level knowledge, understanding, application and evaluation. Affective aspects are seen at the level of acceptance, participants, the formation of life patterns, psychomotor aspects are seen at the level of complex movements, and ordinary movements. In the process of evaluating mathematic learning the teacher also applies Bloom's Taxonomy to the cognitive aspects of the knowledge level. Affective aspects at the level of acceptance, participation, and the formation of patterns of life, aspects of students psychomotor at the level of complex movements. Keywords: Mathematic Learning Approach, Bloom Taxonomy, Primary School